2019
DOI: 10.1016/j.celrep.2019.04.088
|View full text |Cite
|
Sign up to set email alerts
|

CD34+KLF4+ Stromal Stem Cells Contribute to Endometrial Regeneration and Repair

Abstract: SUMMARY The regenerative capacity of the human endometrium requires a population of local stem cells. However, the phenotypes, locations, and origin of these cells are still unknown. In a mouse menstruation model, uterine stromal SM22α + -derived CD34 + KLF4 + stem cells are activated and integrate into the regeneration area, where they differentiate and incorporate into the endometrial epithelium; this process is correlated with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 84 publications
3
63
1
Order By: Relevance
“…Recently, CD34 + KLF + endometrial stromal stem/progenitor cells were identified in the perivascular region in the endometrium of a menstruating mouse model ( Yin et al, 2019 ). They expressed the smooth muscle marker, SM22α, and vimentin and upon estrogen stimulation trans-differentiated into gland-like structures lined with E-cadherin-expressing epithelial cells.…”
Section: Human Endometrial Mscmentioning
confidence: 99%
“…Recently, CD34 + KLF + endometrial stromal stem/progenitor cells were identified in the perivascular region in the endometrium of a menstruating mouse model ( Yin et al, 2019 ). They expressed the smooth muscle marker, SM22α, and vimentin and upon estrogen stimulation trans-differentiated into gland-like structures lined with E-cadherin-expressing epithelial cells.…”
Section: Human Endometrial Mscmentioning
confidence: 99%
“…Moreover, CD34 is a transmembrane phosphoglycoprotein and well-studied marker for hematopoietic stem and progenitor cells. Recently, it has been suggested that CD34 is expressed by vascular endothelial progenitors and endometrial stromal stem cells particularly displaying neovascular formation [26,52]. Immuno uorescence staining of CD31 ( Fig.…”
Section: Intra-uterine Cxcl12 Treatment Promotes Uterine Angiogenesismentioning
confidence: 95%
“…Various substances including granulocyte colony-stimulating factor (G-CSF), mesenchymal stem cells (MSC), and platelet-rich plasma (PRP) have been suggested to enhance endometrial angiogenesis and receptivity for patients who are suffering from implantation failure with poor endometrial receptivity [22][23][24]. However, the e cacy of those substances still has not been fully evidenced yet [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Although the physiological and pathological changes in the endometrium during remodeling are well characterized, the cellular mechanisms that drive the programmed events of the endometrial tissue remodeling are still not completely understood. Recent studies provide evidence for endometrial stem cell (ESC) populations that contribute to endometrial regeneration and repair [14,15]. However, these studies have either used rodent models that does not experience menstrual shedding or artificial mouse models with administration and withdrawal of exogenous progesterone rather than the naturally menstruating women with declining hormone levels caused by the demise of corpus luteum.…”
Section: Introductionmentioning
confidence: 99%